Direct Structural Identification of Gas Induced Gate‐Opening Coupled with Commensurate Adsorption in a Microporous Metal–Organic Framework. Issue 33 (7th July 2016) - Banerjee, Debasis; Wang, Hao; Plonka, Anna M.; Emge, Thomas J.; Parise, John B.; Li, Jing
Abstract: Gate‐opening is a unique and interesting phenomenon commonly observed in flexible porous frameworks, where the pore characteristics and/or crystal structures change in response to external stimuli such as adding or removing guest molecules. For gate‐opening that is induced by gas adsorption, the pore‐opening pressure often varies for different adsorbate molecules and, thus, can be applied to selectively separate a gas mixture. The detailed understanding of this phenomenon is of fundamental importance to the design of industrially applicable gas‐selective sorbents, which remains under investigated due to the lack of direct structural evidence for such systems. We report a mechanistic study of gas‐induced gate‐opening process of a microporous metal–organic framework, [Mn(ina)2 ] (ina=isonicotinate) associated with commensurate adsorption, by a combination of several analytical techniques including single crystal X‐ray diffraction, in situ powder X‐ray diffraction coupled with differential scanning calorimetry (XRD‐DSC), and gas adsorption–desorption methods. Our study reveals that the pronounced and reversible gate opening/closing phenomena observed in [Mn(ina)2 ] are coupled with a structural transition that involves rotation of the organic linker molecules as a result of interaction of the framework with adsorbed gas molecules including carbon dioxide and propane. The onset pressure to open the gate correlates with the extent of such interaction. Abstract : Gate crashing : The gate‐opening mechanism of a microporous metal–organic framework was investigated. The gate‐opening was found to occur though the rotation of organic rings in the presence of specific adsorbates. The energy diagram of gate‐opening is also discussed.